Simulation of Direct Model Reference Adaptive Control on a Coupled-Tank System using Nonlinear Plant Model. - Mahyuddin, Muhammad Nasiruddin; Arshad, Mohd. Rizal; Mohamed, Zaharuddin (2007)
This paper presents the application of direct model reference adaptive control (DMRAC) on a nonlinear model of coupled-tank liquid level control system through simulation.